THE ROLE OF CIVIL SOCIETY ORGANIZATIONS (CSOS) IN ADVOCATING FOR ENVIRONMENTAL JUSTICE IN CASES OF INDUSTRIAL POLLUTION - Taylor, Sarah; Mitchell, Thomas; Johnson, Zoe (Yayasan Adra Karima Hubbi, 2025)
Environmental justice has become a central issue in the global discourse on sustainability, particularly in the context of industrial pollution. Civil society organizations (CSOs) play a pivotal role in advocating for the rights of affected communities, ensuring that the voices of marginalized populations are heard. Despite their significant contributions, the effectiveness of CSOs in promoting environmental justice remains underexplored. This research investigates the role of CSOs in advocating for environmental justice, specifically in cases of industrial pollution, examining their strategies, challenges, and impact on policy change. The study employs a qualitative research design, utilizing in-depth interviews with key stakeholders from selected CSOs, community members, and policymakers. It also involves case study analysis of prominent instances of industrial pollution and CSO involvement in both mitigating the effects and demanding accountability. The findings reveal that CSOs significantly contribute to raising awareness, mobilizing communities, and holding industries accountable for environmental damage. However, challenges such as limited resources, political opposition, and legal barriers hinder their advocacy efforts. The study concludes that while CSOs play a crucial role in environmental justice advocacy, their success is contingent upon strengthening partnerships, increasing access to resources, and fostering greater political will for environmental protection.